The Mexican yam bean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Known as cassava-bean or yam-bean in the Caribbean islands or Pachyrhizus erosus by scientists, is a vegetable that has both the advantages of legumes and root of vegetables. Like root crops, it gves an abundant harvest: 40t per hectare on average...